THE PRESENCE OF COLLABORATION SKILL IN ELT CLASS - Mutohhar Mutohhar; Hakim Sudinpreeda; Agung Dwi Nurcahyo; Fajar Kartika (Prominent, 2020)
One of the skills that must be possessed in the 21st century is collaboration skill. It requires teachers to present or provide it in the learning process, so that later students are expected to be able to implement it in their real life. The study reported in this paper aims to describe the implementation of collaboration skill in the process of teaching and learning. The data collected by means of close-ended questionnaires and guided interview that were administered to 125 freshman students of the English Education Department of Universitas Muria Kudus. The result shows that 84% of the students said that the teacher has implemented the collaboration skill, however from 84%, only 48% is categorized as instructionally effective. It is suggested that the teachers should manage some instructions and control how the instructions are executed. Keywords: 21st century skills, collaboration skill, effective instruction.